Tanggung Jawab Perawat Terhadap Malpraktik - Aka Romli, Ridho'i (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
Nurses, as an integral part of the healthcare workforce, have an important responsibility in providing safe, high-quality, and ethical nursing care. However, in practice, it is not uncommon for nurses to commit negligence or errors that lead to malpractice, causing harm to patients and resulting in legal liability. The background of this study is the increasing number of cases of nurse negligence in healthcare services and the ongoing ambiguity regarding the scope of nurses' responsibilities in medical practice, particularly when performing duties delegated by nurses. This study aims to analyze the form of nurses' responsibility for malpractice incidents in healthcare services and to identify barriers and solutions in the implementation of such responsibilities. The method used in this study is normative legal analysis, along with a court decision study (Decision No. 75/Pid.Sus/2019/PN.Mbo) examining the criminal liability of nurses for medical actions resulting in patient death. Data was obtained through literature review and interviews with healthcare workers and legal officials at Waru Pamekasan General Hospital. The results of the study indicate that nurses' liability in cases of malpractice can include administrative, ethical, and even criminal liability, depending on the type of error committed and the legal consequences incurred. The obstacles faced include nurses' low level of legal understanding, unclear boundaries of authority, excessive workloads, and a lack of legal protection. Proposed solutions include strengthening professional regulations, enhancing legal and ethical training, and implementing transparent reporting and oversight systems. This study underscores the importance of legal protection for nurses while ensuring patient safety in healthcare services.